Electroacupuncture improves cardiac function and reduces infarct size by modulating cardiac autonomic remodeling in a mouse model of myocardial ischemia. Issue 6 (December 2021) - Lu, Sheng-Feng; Wang, Jun-Meng; Yuan, Jing; Yang, Wen-Xiu; Chen, Li-Yao; Zhang, Tao; Jing, Xin-Yue; Zhuang, Yi; Zhang, Cheng-Shun; Fu, Shu-Ping; Yu, Mei-Ling
Background: Sympathetic and parasympathetic nerve remodeling play an important role in cardiac function after myocardial ischemia (MI) injury. Increasing evidence indicates that electroacupuncture (EA) can regulate cardiac function by modulating the autonomic nervous system (ANS), but little is known about its effectiveness on neural remodeling post-MI. Objectives: To investigate the role of EA in ANS remodeling post-MI. Methods: Adult male C57/BL6 mice were equally divided into the Control (Ctrl), MI and EA groups after generating the MI model by ligating the left anterior descending (LAD) coronary artery. Echocardiography and 2, 3, 5-triphenyltetrazolium (TTC) staining were employed to evaluate cardiac function and infarct size after EA treatment for five consecutive days. Serum norepinephrine (NE) levels were measured by ELISA to quantify sympathetic activation. Then, ANS remodeling was detected by immunohistochemistry (IHC), RT-qPCR, and Western blotting. Results: Our preliminary findings showed that EA increased ejection fraction and fractional shortening and reduced infarct area after MI injury. Serum NE levels in the EA group were significantly decreased compared with those in the MI group. IHC staining results demonstrated that the density of growth associated protein (GAP)43 and tyrosine hydroxylase (TH) positive nerve fibers in the EA group were decreased with increased choline acetyltransferase (CHAT) and vesicular acetylcholine transporter (VACHT). Meanwhile, the results verified that mRNA and protein expression of GAP43 and TH were significantly inhibited by EA treatment in the MI mice, accompanied by elevated CHAT and VACHT. Conclusions: EA treatment could improve cardiac function and reduce infarct size by modulating sympathetic and parasympathetic nerve remodeling post-MI, thus helping the cardiac ANS reach a new balance to try to protect the heart from further possible injury.